Influence of heat treatment temperature on structure and exothermic properties of electroless NiP plating carbon fiber heating elements. (15th June 2019) - Choi, Bo-kyung; Choi, Woong-Ki; Rhee, Kyong Yop; Park, Soo-Jin; Seo, Min-Kang
Abstract: In this work, the heating performances of electroless NiP plated carbon fibers (MCF) at different heat treatment temperatures (300, 400, 500, and 700 °C) were investigated using an infrared thermal imaging camera. From the experimental results, we found that the MCF was a mixture of microcrystalline and amorphous phases, as indicated by XRD. In addition to the stable Ni, Ni3 P, and NiO phases, the metastable Ni5 P phase was also observed although the amount was small. A higher heat treatment temperature of 400 °C resulted in the growth of Ni and Ni3 P phases indicated by the stronger peak intensity. However, the specific resistance increased as the heat treatment temperature increased above 400 °C. Accordingly, the performance of heat-treated MCF as electrical heating elements was strongly dependent on the surface structure of the MCF as well as the heat treatment temperature. The MCF exhibited a low electrical heating temperature (31.0 °C), while MCF-H400 exhibited an excellent electrical heating temperature (102.0 °C) along with rapid temperature response and high heat output to maintain a maximum temperature at a given applied voltage. Graphical abstract: The MCF exhibited a low electrical heating temperature (31.0 °C), while MCF-H400 exhibited an excellent electrical heating temperature (102.0 °C) along with rapid temperature response and high heat output to maintain a maximum temperature at a given applied voltage.Image 1 Highlights: The heating performances of electroless NiP plated carbon fibers (MCF) at different heat treatment temperatures were investigated. The grain size of the MCF was increased with increasing the heat treatment temperature and Ni based compounds were formed in the plated. When MCF was heat-treated at 400–500 °C, the heating performances of the MCF improved owing to the lower specific resistance, excellent electrical heating.